Safety Education’s Impact on Exercise Adherence: Experiences from a Swimming Club for People with Disabilities - Seung Ok An; Jin Woo Jung (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Regular exercise is essential for maintaining physical and psychological well-being, particularly among individuals with disabilities. One cannot overstate the importance of safety during sports participation, as it directly impacts exercise adherence and overall health outcomes for this population. This study sought to assess the effects of safety management education on exercise adherence among disabled swimming club participants. It also examined how their sports participation experiences may influence these effects. Through the use of hierarchical regression analysis, structured questionnaires were administered to carers, resulting in data collected from 491 respondents. The results showed that education in safety management has a significant positive impact on athletic performance, exercise habits, and the overall environment. In addition, participating in sports had a positive impact on exercise adherence by enhancing cognitive and behavioural experiences. The presence oo disabled participants clearly demonstrated the need for customised safety education and engagement strategies. The study emphasises the importance of providing thorough safety management education and creating positive sports participation experiences to encourage long-term exercise commitment among disabled individuals. Further investigation should prioritise examining the lasting impacts of these interventions and determining the key factors that have the greatest impact on participants' commitment, thus safeguarding the overall health and well-being of individuals with disabilities by promoting ongoing involvement in sports.